PENGARUH PEMBELAJARAN BERBASIS KONSTRUKTIVISME TERHADAP PEMAHAMAN KOSAKATA SISWA MADRASAH IBTIDAIYYAH - Al Bashir, Muhammad Nizar; Sedya santosa; Asnafiyah; Nurul Imam; Nisa Syuhda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the influence of constructivism-based learning on the vocabulary understanding of Madrasah Ibtidaiyah (MI) students. The method used in this study is an experimental method with a pretest-posttest design. The subjects of the study were MI grade IV students who were divided into two groups: an experimental group that applied constructivism-based learning and a control group that used conventional methods. The results showed that there was a significant improvement in the vocabulary understanding of students who were taught with a constructivist approach compared to the control group. This research is expected to contribute to the development of Indonesian learning methods in MI.